IBM for the Coastal Womens Group in Kecamatan Panjang Kota Bandar Lampung with Problem of Waste Recycle Product Marketing and Minimum Awareness Toward Coastal Environment - Handayani, Dwi Wahyu; Ratnasari, Yuni; Fahmi, Teuku; Nizar, Moh. (Proceeding of International Conference 1st SHIELD 2016, 2016)
Community issues is the awareness and participation of coastal communities about waste management institutionally in Green Village program is still low, the difficulties in marketing of the compost bins refined products and handicrafts, understanding and concerning beyond coastal communities to environmental issues is still low. IbM activity is targeting several things: 1) The activity is intended for residents of women in the Village of Panjang Selatan and Panjang Utara, 2) The coaching carried out some cognitive aspects regarding gender equality, rights and roles, women empowering in the management of coastal environment, institutional strengthening and networking, as well as the optimization of litter processed products. 3) Coaching and mentoring aspects of technology support website. The results of the activities of the counseling is to increase awareness of gender and womens roles of garbage management group in Kecamatan Panjang Selatan and Panjang Utara. In addition, the realization of institutional strengthening groups so that provide assurances to the Village Green activists to continue performing environmental protection issues despite being hampered, and open the horizons for the group to build networks in order to more easily achieve the goal. The indication is the increasing number of women who are active, and more diverse activities. Secondly, establish and managing beneficial website for the introductory of activity and environmental issues in coastal community and place for promoting those refined products. Thirdly, campaigns create awareness about the coastal environment outside the coastal community environmental awareness, and advocacy to coordinate with the local government may be able to build networks with various parties in order to continue the work. Keyword: Coastal Woman, Marketing Product, Waste Recycle, People Awareness